2010
DOI: 10.1258/acb.2010.010068
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone interference in the immunoassay of androstenedione

Abstract: Background: In an evaluation of androstenedione results from patient serum samples using the Siemens Immulite 2500 analyser and manual Coat-A-Count (CAC) methods, three outliers were evident with grossly elevated results in the CAC assay. Methods: The clinic notes of three patients with apparently high serum androstenedione concentrations by the CAC assay were checked for medications. The samples were all from patients with polycystic ovary syndrome taking 100 -200 mg/d of a steroidal antiandrogen (spironolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similarly, Honour et al. [ 46 , 47 ] reported that spironolactone interfered with androstenedione and aldosterone immunoassays because spironolactone is an analog of aldosterone, which may lead to typical physical interference or cross‐reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Honour et al. [ 46 , 47 ] reported that spironolactone interfered with androstenedione and aldosterone immunoassays because spironolactone is an analog of aldosterone, which may lead to typical physical interference or cross‐reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that the androstenedione antibodies in the assay could be reacting with the C/D ring or 7-modified thiol residue of spironolactone or its metabolites. 4 The patient was receiving a low dose of spironolactone, but it is apparent that the dose was sufficient to cause interference because serum androstenedione normalized after withdrawal. The manufacturer suggests that the cross-reaction of spironolactone with androstenedione in this assay is 0Á109%; this implies that our patient's blood spironolactone concentration would have to have been greater than 4000 ng/ml to give this androstenedione result through interference.…”
Section: Sirmentioning
confidence: 99%
“…Dear Editor, Some authors have shown that the encapsulated follicular variant of papillary thyroid carcinoma (E-FVPTC) has a better prognosis than encapsulated classic PTC 1,2 and nonencapsulated FVPTC. 3,4 In patients with PTC restricted to the gland (i.e. without extrathyroid invasion or apparent metastases), lobectomy is considered sufficient for unifocal tumours ≤1 cm, whereas total thyroidectomy followed by 131 I ablation is recommended for tumours >4 cm.…”
Section: Sirmentioning
confidence: 99%